Spousal Support and Marital Satisfaction: The Mediating Role of Gratitude Expression - Ben Amor, Leila; Grigoryan, Mariam (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the direct and indirect relationships between spousal support and marital satisfaction, with gratitude expression as a mediating variable. Methods and Materials: A descriptive correlational design was employed with 370 married individuals from Armenia, selected based on the Morgan and Krejcie sampling table. Data were collected using standardized instruments for marital satisfaction, spousal support, and gratitude expression. Analyses were conducted in two stages: Pearson correlation analysis in SPSS-27 to examine bivariate associations, and Structural Equation Modeling (SEM) in AMOS-21 to test the hypothesized mediating model. Model fit was evaluated using established indices, including χ²/df, GFI, AGFI, CFI, TLI, and RMSEA. Findings: Pearson correlations revealed that spousal support was significantly associated with both marital satisfaction (r = .58, p < .001) and gratitude expression (r = .51, p < .001), while gratitude expression was also correlated with marital satisfaction (r = .46, p < .001). SEM demonstrated acceptable model fit (χ²/df = 1.93, GFI = 0.93, AGFI = 0.91, CFI = 0.96, TLI = 0.95, RMSEA = 0.049). Direct effects showed that spousal support positively predicted marital satisfaction (β = 0.37, p < .001) and gratitude expression (β = 0.44, p < .001), while gratitude expression also predicted marital satisfaction (β = 0.29, p = .001). The indirect effect of spousal support on marital satisfaction through gratitude expression was significant (β = 0.13, p = .002), confirming partial mediation. Conclusion: Findings underscore the dual importance of supportive behaviors and gratitude expression in shaping marital satisfaction. Spousal support enhances satisfaction both directly and indirectly by fostering gratitude, suggesting that couples who both provide support and express appreciation are more likely to sustain fulfilling relationships.